Transmitter design for public transportation tracking system using RFID technology / Abdul Rahman Mohamed Roslan - Mohamed Roslan, Abdul Rahman (2008)
This thesis will focus on obtaining the best possible way to solve the bus transportation problem. The development of tracking the bus locating using Radio Frequency Identification (RFID) system is also describe in this thesis. The importance of RFID in today world is very high, due to its small package and its ability to store data.